PREPARATION OF ENGINEERS FOR PRAXIS BY SUBJECT NAMED METHODOLOGY OF TECHNICAL EXPERIMENT - KASSAKOVA, Viera; MINARIK, Stanislav (Trends in education, 2008)
In presented contribution authors introduce education of subject named Methodology of technical experiment, by graduation of which the sudents of Faculty of Material Science and Technology increase their ability of creative approach to solution of practical problems associated with measuring instruments operating, eventually similar ability.
Keywords: Technical experiment; methodology of experiment; measuring devices; connection theory with pactice